Perancangan Antarmuka Website E-commerce UMKM Pertenunan Pelangi Dengan Metode Design Thinking - Putu Ananta Yoga Manik Mas; Andi Reza Perdanakusuma; Hanifah Muslimah Az-Zahra (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2023)
This research focuses on designing e-commerce website interface that suit user needs so that the design created can be developed into e-commerce websites to increase promotion and marketing for UMKM Pertenunan Pelangi. This research uses the design thinking method which emphasizes the user's perspective in understanding and identifying the needs of users to create effective solutions. This research begins by conducting interviews with prospective users to identify problems which will be determined by solutions. Solutions are determined by brainstorming with stakeholder. After determining the solution, the interface design is visualized. To determine whether the designed interface design is in accordance with user needs, usability testing was conducted by using the think aloud method to 5 participants by using 12 task scenarios. 3 participants were able to complete all the task scenarios, but there were 2 participants who were only able to complete 11 task scenarios. There were also some feedbacks from the participants for the interface design. With that result it can be said that the designed interface design succeeded in overcoming the problems that have been identified.